Cervical penetration rates and efficiency of non-surgical embryo recovery in estrous-synchronized Santa Ines ewes after administration of estradiol ester (benzoate or cypionate) in combination with d-cloprostenol and oxytocin - Fonseca, J. F.; Zambrini, F. N.; Guimaraes, J. D.; Silva, M. R.; Oliveira, M. E. F. [UNESP]; Bartlewski, P. M.; Souza-Fabjan, J. M. G. (Elsevier B.V., 2019)
The effects of estradiol esters, D-cloprostenol and oxytocin on induction of cervical dilation prior to non-surgical embryo recovery in Santa Ines ewes (Days 6-7 estrous cycle) were assessed in this study. In Trial 1, transcervical embryo flushing was performed in estrous-induced ewes administered 37.5 mu g of D-cloprostenol i.m. 10 h before and 50 IU of oxytocin i.v. 20 min before uterine flushing with (EB-PGF-OT; n = 13) or without (PGF-OT; n = 11) 1 mg of estradiol benzoate i.m. administered concurrently with D-cloprostenol injection. In Trial 2, the estrous-synchronized animals were treated with 1 mg of estradiol benzoate (EB-PGF-OT; n = 12) or estradiol cypionate (EC-PGF-OT; n = 12) i.m. along with 37.5 mu g of D-cloprostenol i.m. 16 h before and 50 IU of oxytocin i.v. 20 min before uterine flushing. In Trial 1, uterine flushing could be accomplished in 38% of ewes in the EB-PGF-OT and 27% those in the PGF-OT (P > 0.05) group. Flushing fluid recovery averaged 90% and there were 1.0 +/- 1.1 embryos/ewe collected with mean duration of the flushing procedure being (similar to)36 min. In Trial 2, uterine flushing was accomplished in 78% of ewes in the EB-PGF-OT and 44% of those in the EC-PGF-OT group (P > 0.05) with mean flushing fluid recovery rate being 88% and time elapsing to complete flushing being (similar to)33 min. Within the subsets of animals treated with EB, the percentages of successful transcervical penetrations were 38% compared with 78% in Trials 1 and 2, respectively (i.e., with EB administered 10 h compared with 16 h before uterine flushing: P < 0.05). The interval from EB administration to the beginning of transcervical penetration can affect the efficacy of embryo recovery procedures utilizing a combined EB/d-cloprostenol/oxytocin pre-treatment.
Keywords: Sheep; Cervical dilation; Estradiol esters; Cloprostenol; Oxytocin; Transcervical embryo recovery